Postmortem cesarean: report of our successful neonatal outcomes after severe trauma during pregnancy and review of the literature - YAKUT, KAHRAMAN; Yakut, KAHRAMAN; Guven, Sirin; Yazar, Asami; Aydogan, Huri; Erguven, Muferet; Avci, Eftal (My University, 2012)
Postmortem cesarean is delivering of a child by cesarean section after the death of the mother. A prompt decision for cesarean delivery is very important in such cases. The survival of both the mother and the baby is dependent on a number of factors, including the time between maternal cardiac arrest and delivery, the underlying reasons for the arrest, the location of the arrest and the skills of the medical staffs. The earlier the fetus is delivered following maternal arrest the better is the fetal survival. Cesarean section should be performed no later than 4 minutes after initial maternal arrest. A fetus delivered within 5 minutes from initiation of CPR (cardiopulmonary resuscitation) has the best chance for survival. We reported 2 cases of successful postmortem cesarean section done 45 and 15 minutes after maternal death. The 1st case was a 29-year-old pregnant woman at 37 weeks gestation with cardiopulmonary arrest following gunshot head injuries. The baby survived with neurological sequels and ongoing treatment at our newborn intensive care unit. Second case admitted to the emergency service was a 28-year-old primigravida of 31 weeks gestation with cardiopulmonary arrest due to massive brain and thoracic hemorrhage after a road traffic accident. The baby recovered without neurological sequels.